Comparative analysis of autoantibodies targeting peptidylarginine deiminase type 4, mutated citrullinated vimentin and cyclic citrullinated peptides in rheumatoid arthritis: associations with cytokine profiles, clinical and genetic features - Reyes-Castillo, Z (Clin Exp Immunol, 2015)
Antibodies against cyclic citrullinated peptides (anti-CCP) are widely used for diagnosis of rheumatoid arthritis (RA). We performed a comparative analysis of antibodies targeting the citrullinating enzyme peptidylarginine deiminase type 4 (anti-PAD4) and mutated citrullinated vimentin (anti-MCV) with anti-CCP autoantibodies in RA patients and examined their relationships with clinical parameters, cytokine profiles and the PADI4 gene. Autoantibodies were examined by enzyme-linked immunosorbent assay (ELISA) in sera of 170 RA patients and 103 controls. Cytokine profiles were measured using a multiplex system. PADI4 polymorphisms (89G > A, 90T > C and 92G > C) were genotyped by polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP). Anti-PAD4, anti-MCV and anti-CCP autoantibodies were detected in 24, 61 and 74% of RA patients, respectively. Positive correlations were observed between anti-PAD4 and disease duration; anti-CCP and erythrocyte sedimentation rate (ESR); anti-MCV and ESR and C-reactive protein. Anti-MCV antibodies were associated with high disease activity score 28 (DAS-28) in early RA. Concentrations of T helper type 1 (Th1) [tumour necrosis factor (TNF)-α, interleukin (IL)-12, IL-2, IL-1β], Th2 (IL-4, IL-6, IL-10, IL-13) and Th17 (IL-17) cytokines were higher in RA than in controls. Th2 and, to a lesser extent, Th1-related cytokines, showed positive correlations with anti-MCV and anti-CCP. The GTG haplotype in PADI4 was associated with anti-CCP and anti-MCV, but not anti-PAD4 antibodies. In conclusion, anti-PAD4 antibodies are detected mainly in established RA, which is in contrast to the early detection of antibodies against citrullinated peptide/proteins (ACPAs). Among autoantibodies, anti-MCV appear to perform better as markers of disease activity. Furthermore, anti-CCP and anti-MCV are associated genetically with the citrullinating enzyme PAD4 and are related strongly to Th1 and Th2 cytokines, suggesting a feed-forward loop between cytokines and ACPA production.